2020
DOI: 10.1111/jcmm.16061
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐223‐3p inhibits rTp17‐induced inflammasome activation and pyroptosis by targeting NLRP3

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…Huang et al found that H 2 S suppressed HG-induced cardiomyocyte inflammation and apoptosis by inhibiting the TLR4/NF-κB pathway and its downstream NLRP3 inflammasome activation [26]. Studies from other group also revealed DM-induced arrhythmias could be successfully treated by inhibiting the IL-1β axis with either IL-1 receptor antagonist or by inhibiting the NLRP3 inflammasome [27,28]. In fact, different concentrations of H 2 O 2 have different Reactive oxygen species (ROS) serves as important inflammation activating signals.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al found that H 2 S suppressed HG-induced cardiomyocyte inflammation and apoptosis by inhibiting the TLR4/NF-κB pathway and its downstream NLRP3 inflammasome activation [26]. Studies from other group also revealed DM-induced arrhythmias could be successfully treated by inhibiting the IL-1β axis with either IL-1 receptor antagonist or by inhibiting the NLRP3 inflammasome [27,28]. In fact, different concentrations of H 2 O 2 have different Reactive oxygen species (ROS) serves as important inflammation activating signals.…”
Section: Discussionmentioning
confidence: 99%
“… 67 Moreover, a study involving Treponema pallidum subspecies pallidum (T pallidum) infection showed that a dramatic reduction in the serum levels of miR-223-3p of patients with syphilis compared with healthy controls, which could target NLRP3 to suppress inflammasome activation and pyroptosis in T pallidum-induced Human Umbilical Vein Endothelial Cells (HUVECs), thus indicating a potential target for syphilis-induced endothelial injury. 68 …”
Section: The Roles Of Ncrnas In Inflammasomes Activation In Inflammatory Diseasesmentioning
confidence: 99%
“…67 Moreover, a study involving Treponema pallidum subspecies pallidum (T pallidum) infection showed that a dramatic reduction in the serum levels of miR-223-3p of patients with syphilis compared with healthy controls, which could target NLRP3 to suppress inflammasome activation and pyroptosis in T pallidum-induced Human Umbilical Vein Endothelial Cells (HUVECs), thus indicating a potential target for syphilis-induced endothelial injury. 68 Apart from targeting NLRP3 directly, ncRNAs can also regulate the NLRP3 inflammasome activation process. The NLRP3 inflammasome can be activated by a diverse range of stimuli and a 2-signal model has been proposed for to explain this process (Figure 3).…”
Section: The Roles Of Ncrnas In Regulating Inflammasomes Activation In Different Types Of Microbial Infectionmentioning
confidence: 99%
“…Previously, it was found that NLRP3 is one of the target genes of miR-223 (Bauernfeind et al, 2012). Recent studies have confirmed that miR-223 can inhibit inflammation by targeting NLRP3, thereby suppressing inflammasome activation and pyroptosis in T palliduminfected endothelial cells (Long et al, 2020), limiting inflammation in human dental pulp fibroblasts (Wang et al, 2020), relieving spinal cord injury (Zhang et al, 2020), and modulating dendritic cell function to ameliorates autoimmune myocarditis (Zhou et al, 2017). However, the status of miR-223 expression and the potential role of miR-223 in gout have not been reported.…”
Section: Introductionmentioning
confidence: 96%
“…MicroRNAs (miRs) are short non-coding RNAs with a length of approximately 22 nucleotides. Recently, the role of miRs in negatively regulating inflammation in autoimmune diseases and inflammation disorders has received increasing attention (Henshall et al, 2016;Long et al, 2020). miR-223 is expressed in myeloid cells, and miR-223 under-expression is associated with many diseases, including leukemia, hepatitis B, influenza, lymphoma, and inflammation (Gilicze et al, 2014).…”
Section: Introductionmentioning
confidence: 99%